Implications of CpG islands on chromosomal architectures and modes of global gene regulation. Issue 9 (26th February 2018) - Beck, Samuel; Rhee, Catherine; Song, Jawon; Lee, Bum-Kyu; LeBlanc, Lucy; Cannon, Laurie; Kim, Jonghwan
Abstract: CpG islands (CGIs) have long been implicated in the regulation of vertebrate gene expression. However, the involvement of CGIs in chromosomal architectures and associated gene expression regulations has not yet been thoroughly explored. By combining large-scale integrative data analyses and experimental validations, we show that CGIs clearly reconcile two competing models explaining nuclear gene localizations. We first identify CGI-containing (CGI+) and CGI-less (CGI−) genes are non-randomly clustered within the genome, which reflects CGI-dependent spatial gene segregation in the nucleus and corresponding gene regulatory modes. Regardless of their transcriptional activities, CGI+ genes are mainly located at the nuclear center and encounter frequent long-range chromosomal interactions. Meanwhile, nuclear peripheral CGI− genes forming heterochromatin are activated and internalized into the nuclear center by local enhancer–promoter interactions. Our findings demonstrate the crucial implications of CGIs on chromosomal architectures and gene positioning, linking the critical importance of CGIs in determining distinct mechanisms of global gene regulation in three-dimensional space in the nucleus.